Beyond technology adoption: How artificial intelligence and teacher competence shape learning quality in religious education - Komang Sutawan (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2025)
The rapid advancement of Artificial Intelligence in Education (AIEd) has generated growing expectations for improving learning quality. However, evidence suggests that technological innovation alone is insufficient without adequate teacher competence, particularly in value-based and religious education contexts. This study investigates the effects of Artificial Intelligence in Education and teacher competence on learning quality in Buddhist Religious Education schools in Lampung Province, Indonesia, an underrepresented educational setting characterized by limited institutional resources and digital infrastructure. Employing a quantitative survey design, data were collected through validated questionnaires administered to all 76 Buddhist school teachers in the province using a census sampling technique. Multiple linear regression analysis was applied to examine both partial and simultaneous relationships among Artificial Intelligence, teacher competence, and learning quality. The findings indicate that Artificial Intelligence in Education has a significant positive effect on learning quality when analyzed independently. Teacher competence, encompassing pedagogical, professional, and digital dimensions, also shows a strong and significant influence on learning quality. However, when both variables are analyzed simultaneously, teacher competence emerges as the dominant predictor, while the direct effect of Artificial Intelligence becomes statistically non-significant. This suggests that the educational value of AI is largely contingent upon teachers’ competencies in integrating technology into meaningful instructional practices. The study concludes that Artificial Intelligence functions as an instructional support tool rather than an independent driver of learning improvement. These findings underscore the importance of aligning technological innovation with continuous teacher professional development to achieve sustainable improvements in learning quality within religious education contexts.